2014
DOI: 10.1245/s10434-014-4058-y
|View full text |Cite
|
Sign up to set email alerts
|

Rare Metastases of Well-Differentiated Thyroid Cancers: A Systematic Review

Abstract: WDTC can manifest with highly variable and unusual clinical features. Rare sites of metastases should be considered in the absence of the more common extra-cervical disease recurrence locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 20 publications
2
62
0
1
Order By: Relevance
“…In fact, metastatic PTCs account for <0.6% of all malignant pleural effusions. 9 The diagnosis of malignant pleural effusion due to thyroid primary is prognostically important as it is associated with decrease in median survival to as low as 10 months. 8 The reason is probably because most thyroid carcinomas are well differentiated papillary carcinomas which have a propensity for lymph node metastasis and distant metastases are relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, metastatic PTCs account for <0.6% of all malignant pleural effusions. 9 The diagnosis of malignant pleural effusion due to thyroid primary is prognostically important as it is associated with decrease in median survival to as low as 10 months. 8 The reason is probably because most thyroid carcinomas are well differentiated papillary carcinomas which have a propensity for lymph node metastasis and distant metastases are relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these were follicular and 2 were papillary carcinomas (13). As already stated above, by the year 2015, less than 25 cases had been published in medical literature (9,11).…”
Section: Discussionmentioning
confidence: 86%
“…However, the detection of these metastases during life is very rare (2,10). By the year 2015, less than 25 cases of renal metastases from thyroid cancer were reported in the English-language literature, with most of the subjects being female and over 45 years of age (5,9,11). Seven patients had conventional PTC, 6 had a follicular variant of PTC, and 11 had FTC (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review by Madani and coworkers (14) revealed that, among 492 patients with differentiated thyroid cancer and rare sites of end-organ distant metastases, the brain was the most commonly affected organ within the rare locations. In 1986, McConahey and coworkers (15) verified that 15% of the patients with metastatic papillary thyroid carcinoma developed CNS metastases along their disease course.…”
Section: Discussionmentioning
confidence: 99%